Program Kunjungan Perpustakaan Terjadwal sebagai Upaya Memotivasi Literasi Membaca Siswa Sekolah Dasar - Fernando Eka Saputra; Nenes Pujiastuti; Eka Nurlita Sari; Yohannes Kurniawan Barus; Abdul Hamid (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Low reading literacy motivation among elementary school students in Indonesia is an issue requiring systematic and structured intervention. This community service initiative aims to describe the implementation of a scheduled library visit program designed to boost the reading literacy motivation of students in grades 1 through 5 at SDN 1 Karangtengah. The study employed the Asset-Based Community Development (ABCD) approach, leveraging existing school assets such as the library, book collection, teacher support, and student enthusiasm. The program was designed collaboratively with teachers and librarians, featuring one scheduled weekly visit per class over a four-week period. A total of 123 students participated, selected via total sampling. Data collection instruments included reading reflection sheets, observation checklists, and semi-structured interview guides. Data were analyzed using descriptive statistics and thematic analysis. Results indicated a very high level of participation: 112 out of 123 students (91.1%) successfully completed all visit sessions and submitted four fully completed reflection sheets. Full participation rates per class ranged from 86.4% to 92.6%, demonstrating a consistent impact across grade levels. The program's success was facilitated by a consistent visit schedule, a reward system, and reflection sheets tailored to the students' cognitive levels. It is recommended that this program be adopted as a routine school activity to strengthen the literacy culture and be further evaluated using pre-test and post-test designs in schools with diverse characteristics.